Latha Menon (Executive Editor). Microsoft Encarta Encyclopedia Deluxe 2000 - Louw, Phillip (Lexikos, 2000)
In the highly competitive world of CD-ROM encyclopaedias, Microsoft has consistently outperformed its competitors with products for the whole family. Microsoft Encarta Encyclopedia Deluxe 2000 (henceforth Encarta 2000) is the latest flagship of this line of products. The millennium edition is said to be "a modern reference resource that provides a richness of learning experience for people of all ages that extends far beyond what was possible with traditional reference works" (Letter from the editor). This claim reflects the feature which sets CDROM encyclopaedias apart from their printed equivalents - their accessibility. The executive editor emphasizes accessibility as one of the central values of the editorial staff of Encarta 2000.